Short Communication: Chemical composition, antioxidant and antimicrobial activity of Fagonia longispina (Zygophyllaceae) of Algerian (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Ziane L, Djellouli M, Berghioua A. 2021. Short Communication: Chemical composition, antioxidant and antimicrobial activity of Fagonia longispina (Zygophyllaceae) of Algerian. Biodiversitas 22: 3448-3453. The study's aim is to discover the antioxidant, antibacterial efficacy and identifying the main constituents of the essential oil of Fagonia longispina from southwest of Algeria. The essential oil from the aerial parts of the endemic plant Fagonia longispina collected from the region of Sahara southwest of Algeria was isolated by hydrodistillation and analyzed by gas chromatography-mass spectrometry.  Our work was designed then, to evaluate the antioxidant activity of the essential oil of Fagonia longispina by DPPH free radical scavenging and HPTLC techniques. Antibacterial potency of essential oil from this plant has been tested against Staphylococcus aureus (ATCC 29213), Escherichia coli (ATCC 25922), and Bacillus cereus (ATCC11778) by disk diffusion assay. We found that the chemical profile of the essential oil revealed the presence of 14 compounds: Trans–Pinocarveol (3.14 %), Panisaldehyd (4.24 %), Trans geraniol (3.05 %), carvacrol 18.72 %), Elemicin (22.85 %), (Z,E) Farnesol (15.69 %), Caryophyllene oxide (2.68 %), Alpha-curcumene (1.75 %), Germacrene D (4.22 %), longipinane (2.89 %) and ?-Terpinine (2.74 %). The antioxidant assay showed that the essential oil could scavenge DPPH (IC50 values of 2.1959 mg/mL free radical. The essential oil exhibits very effective antimicrobial activity using disk diffusion assay method with minimum inhibitory concentration ranging from 0.75 ?L/mL to 1.9714 ?L/mL. These results showed that this native plant may be a good candidate for further biological and pharmacological investigations.
Keywords: Essential oil, Fagonia Longispina, Antimicrobial activity, Gas chromatography–mass spectrometry analysis